A kind of waterproof fog PVC plastic and its preparation method

By using modified cyclodextrin and EVA-styrene-hydroxyacrylate copolymer in PVC plastics to incorporate anti-fog agents, the problem of fast anti-fog migration rate in waterproof mist PVC plastics is solved, and long-term anti-fog effect and improved mechanical properties are achieved.

CN119286163BActive Publication Date: 2025-03-25ZHEJIANG JINLIDA NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411511133.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-03-25
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

The migration rate of anti-fog agents in existing waterproof mist PVC plastics is fast, resulting in a shorter time-consuming effect and it is difficult to achieve long-term anti-fog effect.

Method used

By doping modified cyclodextrin and EVA-styrene-hydroxyacrylate copolymers in PVC plastics, the inclusion and sustained release anti-fog agents reduces their migration rate and prolongs the aging of anti-fog action.

Benefits of technology

It realizes the long-term anti-fog effect of waterproof mist PVC plastic, improves the transparency and mechanical properties of the product, and extends the service life of the anti-fog agent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to the field of polyvinyl chloride materials, and specifically discloses a fog-proof PVC plastic and a preparation method thereof. The raw materials of the PVC plastic include: 100 parts of polyvinyl chloride resin, 1-2 parts of heat stabilizer, 0.5-2 parts of lubricant, 2-4 parts of anti-fog agent, and 1-2 parts of anti-fog auxiliary agent; the raw materials of the anti-fog auxiliary agent include cyclodextrin, diisocyanate and polyol fatty acid ester in a molar ratio of 1:5-12:8-15, and the number of hydroxyl groups of the polyol fatty acid ester is 1. The PVC plastic of the present application has excellent long-term fog-proof performance. It can ensure the transparency of PVC products in high humidity environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of polyvinyl chloride materials, and in particular to a fog-proof PVC plastic and a preparation method thereof. Background Art

[0002] Transparent PVC products such as helmets and goggles in sports equipment and agricultural greenhouse films not only need to have excellent transparency, but also good anti-fogging properties to ensure that the film surface can maintain a clear field of view and reduce safety hazards under conditions of large temperature differences and high humidity.

[0003] To solve this problem, anti-fog PVC plastics came into being. The core of this product is to precisely blend PVC resin with anti-fog agents (the main component is non-ionic surfactants) and other additives. These non-ionic surfactants can gradually migrate and precipitate to the surface of the product, and form an extremely thin and uniform hydrophilic film on the surface of the PVC plastic through their hydrophilic ends. When water vapor contacts this hydrophilic film, due to the hydrophilic properties of the film, the water vapor will quickly spread into a continuous and transparent water film, rather than condensing into tiny water droplets that affect the line of sight, thereby achieving an anti-fog effect and ensuring the transparency of the product surface. However, the anti-fog agents currently used generally have the problems of fast migration and precipitation rate and short duration of action, making it difficult to achieve a long-term anti-fog effect of the product. Summary of the invention

[0004] In order to alleviate the problem that the current anti-fog agent has a fast migration rate in PVC plastic, resulting in a short anti-fog effect of transparent PVC products, the present application provides a fog-proof PVC plastic and a preparation method thereof.

[0005] In a first aspect, the present application provides a fog-proof PVC plastic, which includes the following raw materials in parts by weight:

[0006] 100 parts of polyvinyl chloride resin, 1-2 parts of heat stabilizer, 0.5-2 parts of lubricant, 2-4 parts of antifogging agent, 1-2 parts of antifogging auxiliary agent;

[0007] The raw materials of the anti-fogging auxiliary agent include cyclodextrin, diisocyanate and fatty acid polyol ester in a molar ratio of 1:5-12:8-15, and the fatty acid polyol ester has 1 hydroxyl group.

[0008] Preferably, the fatty acid polyol ester is diglyceride, and the carbon number of the fatty acid is 10-20.

[0009] Preferably, the diisocyanate is selected from one or more of toluene diisocyanate, diphenylmethane diisocyanate and hexamethylene diisocyanate.

[0010] Preferably, the cyclodextrin molecule contains 6 to 8 D-pyranose glucose units; wherein the cyclodextrins having 6, 7, and 8 D-pyranose glucose units are α-cyclodextrin, β-cyclodextrin, or γ-cyclodextrin, respectively.

[0011] Cyclodextrin is a cyclic compound with an inner cavity structure capable of encapsulating small molecular components. The present invention can achieve the encapsulation of part of the antifogging agent by doping cyclodextrin in PVC plastic, thereby inhibiting the migration rate of the antifogging agent and achieving a slow-release effect.

[0012] It should be noted that the outer surface of cyclodextrin has strong hydrophilicity, poor compatibility in the PVC resin matrix, easy to agglomerate, and difficult to exert its inhibitory effect on the migration of anti-fog agents. For this reason, the present application uses fatty acid polyol ester molecules with only one hydroxyl group to modify cyclodextrin, which can improve the hydrophobicity of cyclodextrin and improve its solubility in PVC resin. Specifically, through the cross-linking effect of diisocyanate, fatty acid polyol esters are grafted onto the surface of cyclodextrin to introduce hydrophobic fatty alkyl chains, which, on the one hand, can improve compatibility and promote the effective dispersion of anti-fog additives; on the other hand, the anti-fog additive has a certain plasticizing effect, which can reduce the interaction force between PVC molecules and improve its flexibility.

[0013] It should be noted that the fatty acid polyol ester molecule can be prepared by esterification reaction of fatty acids and polyols, and the number of active hydroxyl groups in its molecular chain depends on the molar ratio of the fatty acid used in its preparation to the alcohol hydroxyl group in the polyol. When the fatty acid polyol ester molecule contains multiple hydroxyl groups, the chain segment grafted to cyclodextrin has a strong hydrophilicity and cannot effectively improve the compatibility and plasticizing effect. In addition, the carbon number of the fatty acid in the above-mentioned fatty acid polyol ester of the present application is preferably 10 to 20, and the alkyl chain length is suitable, which is conducive to ensuring the plasticizing effect of the obtained anti-fog additive.

[0014] Preferably, the preparation method of the anti-fog auxiliary agent is as follows:

[0015] Add fatty acid polyol ester and diisocyanate to an organic solvent, heat to 50-60°C, stir and reflux at constant temperature for 1-2 hours, add cyclodextrin, heat to 60-80°C, stir and reflux at constant temperature for 3-7 hours; after the reaction is completed, reflux and wash with acetone, distill and recover the solvent after washing, and then dry the product to obtain.

[0016] Preferably, the organic solvent is dimethyl sulfoxide or N,N-dimethylformamide.

[0017] In the above preparation process, the fatty acid polyol ester reacts with the diisocyanate in advance and then reacts with the cyclodextrin, which helps to obtain an anti-fog additive with higher dispersibility and reduce agglomerates.

[0018] Preferably, the antifogging agent is fatty acid polyol ester and / or fatty acid polyoxyethylene ester.

[0019] Preferably, the carbon number of the fatty acid in the fatty acid polyol ester and fatty acid polyoxyethylene ester is not less than 16, more preferably not less than 20.

[0020] The anti-fog auxiliary agent has a good inclusion complexing effect on the anti-fog agent, which helps to improve the slow-release long-acting anti-fog effect. And the anti-fog agent preferably uses fatty acid polyol esters or polyoxyethylene fatty acid esters containing multiple hydroxyls to improve its hydrophilicity. In addition, the longer the number of carbon atoms in the fatty alkyl chain segment, the slower the precipitation rate.

[0021] Preferably, the raw material of the PVC plastic also includes 10 to 20 parts of EVA-styrene-hydroxyacrylate copolymer.

[0022] Preferably, the EVA-styrene-hydroxyacrylate copolymer is obtained by melt grafting reaction of EVA, styrene and hydroxyacrylate in a mass ratio of 100:10-20:5-12 under the action of an initiator, and the reaction temperature is 160-190°C.

[0023] Preferably, the hydroxyacrylate is selected from one or more of hydroxyethyl methacrylate, hydroxyethyl acrylate, hydroxypropyl methacrylate, hydroxypropyl acrylate, hydroxybutyl methacrylate, and hydroxybutyl acrylate.

[0024] Preferably, the VA content in the EVA is 10-30%, which has good transparency and flexibility and helps to ensure compatibility with PVC resin.

[0025] Preferably, the amount of the initiator used is 1-2% of the total mass of EVA, styrene and hydroxy acrylate.

[0026] Preferably, the initiator is a high temperature resistant initiator having a decomposition temperature greater than 160° C. Typically but not restrictively, the initiator is one or more of diisopropyl peroxide, di-tert-butyl peroxide, diethylhexyl peroxide, and tert-butyl dilaurate peroxide.

[0027] The EVA-styrene-hydroxy acrylate copolymer is used to form a polar dispersed phase in the PVC resin substrate, thereby enhancing the resin's ability to bind the antifogging agent, reducing its migration rate, and improving the long-term antifogging effect. Among them, the hydroxy acrylate provides polar groups for the copolymer, and styrene is used to improve the compatibility of the copolymer and PVC. EVA can not only improve polarity and compatibility, but its participation in copolymerization can give the copolymer a toughening effect, which helps to improve the flexibility of PVC plastics and is conducive to the processing of products such as goggles that have high requirements for bendability and toughness.

[0028] Preferably, the heat stabilizer is an organotin heat stabilizer.

[0029] Exemplarily, the organotin heat stabilizer is a methyltin mercaptan compound.

[0030] Preferably, the lubricant is polyethylene wax or oxidized polyethylene wax.

[0031] In a second aspect, the present application provides a method for preparing a fog-proof PVC plastic, comprising the following steps:

[0032] According to any of the above-mentioned raw material ratios of PVC plastic, weigh PVC resin, heat stabilizer, antifogging agent, antifogging aid, and lubricant and add them into a mixer, heat to 110-130° C. and mix evenly, then pass into a cooling mixer and cool and discharge;

[0033] The cooled blended material is passed into a twin-screw extruder for melt extrusion and granulation to obtain anti-fog PVC plastic.

[0034] Preferably, EVA-styrene-hydroxyacrylate copolymer is also added into the mixer.

[0035] In summary, this application has the following beneficial effects:

[0036] The present application grafts fatty acid polyol esters onto cyclodextrins through diisocyanate crosslinkers, introduces fatty alkyl groups on the surface of cyclodextrins, and obtains cyclodextrins that can be evenly dispersed in PVC resins, and the inner cavity of the cyclodextrins can contain small molecule antifogging agents to achieve corrosion inhibition and anti-migration effects, thereby improving the long-term effectiveness of the antifogging agents. Furthermore, the present application forms a polar dispersed phase in PVC plastics by adding EVA-styrene-hydroxyacrylate copolymers, and can form hydrogen bonds with the antifogging agents through the dispersed phases, thereby reducing the migration rate of the antifogging agents and extending the timeliness of the antifogging effect of PVC plastics. DETAILED DESCRIPTION

[0037] Preparation Example 1-1, anti-fog additive, prepared according to the following method:

[0038] Dissolve 12.5 mol of dilaurin and 9 mol of toluene diisocyanate in dimethyl sulfoxide, heat to 55°C, stir and reflux at constant temperature for 1.5 hours, add 1 mol of β-cyclodextrin, heat to 75°C, stir and reflux at constant temperature for 4 hours, reflux and wash the product with acetone after 4 hours, distill and recover the solvent after washing, and then place the product in a vacuum drying oven and dry it at 50°C.

[0039] Preparation Example 1-2, anti-fog additive, prepared according to the following method:

[0040] 8.3 mol of distearic acid glyceryl and 5 mol of hexamethylene diisocyanate are dissolved in dimethyl sulfoxide, the temperature is raised to 50°C, and the mixture is refluxed with constant stirring for 2 hours. 1 mol of β-cyclodextrin is added, the temperature is raised to 65°C, and the mixture is refluxed with constant stirring for 7 hours. The product is washed with acetone after reflux, and the solvent is recovered by distillation after washing. The product is then placed in a vacuum drying oven and dried at 50°C.

[0041] Preparation Example 1-3, anti-fog additive, prepared according to the following method:

[0042] Dissolve 14.6 mol of distearic acid glyceryl and 11.2 mol of toluene diisocyanate in N,N-dimethylformamide, heat to 60°C, stir and reflux at constant temperature for 1 hour, add 1 mol of β-cyclodextrin, heat to 80°C, stir and reflux at constant temperature for 6 hours, and wash the product with acetone after reflux. After washing, distill and recover the solvent, and then place the product in a vacuum drying oven and dry it at 50°C.

[0043] Preparation Example 1-4, anti-fog additive, prepared according to the following method:

[0044] Dissolve 10 mol of dilaurin and 8 mol of toluene diisocyanate in dimethyl sulfoxide, heat to 55°C, stir and reflux at constant temperature for 1 hour, add 1 mol of α-cyclodextrin, heat to 72°C, stir and reflux at constant temperature for 5 hours, and wash the product with acetone after reflux. After washing, distill and recover the solvent, and then place the product in a vacuum drying oven and dry it at 50°C.

[0045] Preparation Example 1-5, anti-fog auxiliary agent, is different from Preparation Example 1-1 in that an equal amount of glyceryl monolaurate is used to replace glyceryl dilaurate.

[0046] Preparation Example 1-6, anti-fog aid, is different from Preparation Example 1-2 in that glyceryl distearate is replaced by an equal amount of glyceryl monostearate.

[0047] Preparation Example 2-1, EVA-styrene-hydroxyacrylate copolymer, prepared according to the following method:

[0048] 10 kg of EVA resin (VA content 18%, melt index 2.5 g / 10 min), 1.6 kg of styrene, and 0.9 kg of hydroxyethyl acrylate were added into a high-speed mixer and mixed for 10 min to obtain a premix.

[0049] Take 0.2kg of diethylhexyl peroxide and 1kg of hexane to prepare an initiator solution, then add the initiator solution and premix into a high-speed mixer and mix for 10 minutes. After mixing evenly, add it into a twin-screw extruder for melt grafting reaction. After reacting for 10 minutes, extrude, cool and granulate to obtain the product. The reaction temperatures of each section of the screw are: 160℃, 175℃, 185℃, 190℃, 185℃, 170℃.

[0050] Preparation Example 2-2, EVA-styrene-hydroxyacrylate copolymer, prepared according to the following method:

[0051] 10 kg of EVA resin (VA content 26%, melt index 7.5 g / 10 min), 1.1 kg of styrene, and 0.5 kg of hydroxyethyl acrylate were added into a high-speed mixer and mixed for 10 min to obtain a premix.

[0052] Take 0.16kg of diisopropylbenzene peroxide and 1kg of acetone to prepare an initiator solution, then add the initiator solution and premix into a high-speed mixer and mix for 20 minutes. After mixing evenly, add it into a twin-screw extruder for melt grafting reaction. After reacting for 10 minutes, extrude, cool and granulate to obtain the product. The reaction temperatures of each section of the screw are: 150℃, 165℃, 180℃, 190℃, 185℃, 180℃.

[0053] Preparation Example 2-3, EVA-styrene-hydroxyacrylate copolymer, prepared according to the following method:

[0054] 10 kg of EVA resin (VA content 16%, melt index 1.5 g / 10 min), 1.8 kg of styrene, and 1.2 kg of hydroxybutyl acrylate were added into a high-speed mixer and mixed for 10 min to obtain a premix.

[0055] Take 0.2kg of diethylhexyl peroxide and 1kg of hexane to prepare an initiator solution, then add the initiator solution and premix into a high-speed mixer and mix for 10 minutes. After mixing evenly, add it into a twin-screw extruder for melt grafting reaction. After reacting for 15 minutes, extrude, cool and granulate to obtain the product. The reaction temperatures of each section of the screw are: 160℃, 170℃, 185℃, 190℃, 185℃, 170℃.

[0056] Preparation Example 2-4, EVA-styrene-hydroxyacrylate copolymer, is different from Preparation Example 2-1 in that hydroxyethyl acrylate is replaced by an equal amount of styrene.

[0057] Preparation Example 2-5, EVA-styrene-hydroxyacrylate copolymer, is different from Preparation Example 2-1 in that styrene is replaced by an equal amount of hydroxyethyl acrylate.

[0058] Example 1, a fog-proof PVC plastic, is prepared according to the following steps:

[0059] Weigh 10kg SG-5 polyvinyl chloride resin (Anhui Huasu SG5-1), 0.15kg dimethyl dithiol methyl tin, 0.12kg oxidized polyethylene wax (softening point 105°C), 0.33kg glyceryl monostearate, 0.16kg anti-fog additive of Preparation Example 1-1, and 1.5kg EVA-styrene-hydroxyacrylate copolymer of Preparation Example 2-1 and add them into a high-speed mixer, heat to 120°C and mix for 10 minutes, then enter into a cooling mixer, and when the temperature reaches 40°C, cool and discharge to obtain a blend.

[0060] The blended material is passed into a twin-screw extruder for melt extrusion, cooling and granulation. The temperature of each section during extrusion is set at: 160°C, 175°C, 180°C, 190°C, 185°C and 170°C.

[0061] Example 2, a fog-proof PVC plastic, is prepared according to the following steps:

[0062] Weigh 10kg SG-5 polyvinyl chloride resin (Anhui Huasu SG5-1), 0.1kg dimethyl dithiol methyl tin, 0.2kg oxidized polyethylene wax (softening point 105°C), 0.24kg glyceryl monostearate, 0.12kg anti-fog additive of Preparation Example 1-2, and 2kg EVA-styrene-hydroxyacrylate copolymer of Preparation Example 2-2, add them into a high-speed mixer, heat to 130°C and mix for 5 minutes, then enter into a cooling mixer, and when the temperature reaches 50°C, cool and discharge to obtain a blend.

[0063] The blended material is passed into a twin-screw extruder for melt extrusion, cooling and granulation. The temperature of each section during extrusion is set at: 150°C, 165°C, 175°C, 190°C, 180°C and 170°C.

[0064] Example 3, a fog-proof PVC plastic, is prepared according to the following steps:

[0065] Weigh 10kg SG-7 polyvinyl chloride resin (Anhui Huasu SG5-1), 0.18kg dimethyl dithiol methyl tin, 0.06kg oxidized polyethylene wax (softening point 105°C), 0.4kg monopalmitic acid glycerol, 0.2kg anti-fog additive of Preparation Example 1-3, and 1.1kg EVA-styrene-hydroxyacrylate copolymer of Preparation Example 2-3 and add them into a high-speed mixer, heat to 120°C and mix for 10 minutes, then enter into a cooling mixer, and when the temperature reaches 40°C, cool and discharge to obtain a blend.

[0066] The blended material is passed into a twin-screw extruder for melt extrusion, cooling and granulation. The temperature of each section during extrusion is set to: 160°C, 170°C, 175°C, 185°C, 185°C, 175°C.

[0067] Example 4, a fog-proof PVC plastic, is different from Example 1 in that the anti-fog agent of Preparation Example 1-1 is replaced by an equal amount of the anti-fog agent of Preparation Example 1-4.

[0068] Example 5, a fog-proof PVC plastic, is different from Example 1 in that the EVA-styrene-hydroxyacrylate copolymer of Preparation Example 2-1 is replaced by an equal amount of the EVA-styrene-hydroxyacrylate copolymer of Preparation Example 2-4.

[0069] Example 6, a fog-proof PVC plastic, is different from Example 1 in that the EVA-styrene-hydroxyacrylate copolymer of Preparation Example 2-1 is replaced by an equal amount of the EVA-styrene-hydroxyacrylate copolymer of Preparation Example 2-5.

[0070] Example 7, a fog-proof PVC plastic, differs from Example 1 in that the EVA-styrene-hydroxyacrylate copolymer of Preparation Example 2-1 is replaced by an equal amount of EVA resin (VA content 18%, melt index 2.5 g / 10 min).

[0071] Comparative Example 1, a fog-proof PVC plastic, is different from Example 5 in that the anti-fog additive of Preparation Example 1-1 is replaced by an equal amount of the anti-fog additive of Preparation Example 1-5.

[0072] Comparative Example 2 is a fog-proof PVC plastic, which is different from Example 5 in that the anti-fog additive of Preparation Example 1-1 is replaced by an equal amount of the anti-fog additive of Preparation Example 1-6.

[0073] Comparative Example 3, a fog-proof PVC plastic, is different from Example 5 in that the anti-fog additive of Preparation Example 1-1 is replaced by an equal amount of β-cyclodextrin.

[0074] The following is an explanation of the effect of this application through experiments:

[0075] 1. Mechanical properties test: The tensile strength and elongation at break of the PVC plastics in the above examples and comparative examples were tested in accordance with the requirements of GB / T 1040-1992 "Test Method for Tensile Properties of Plastics". The tensile strength is used to characterize the rigidity of the PVC plastic, and the elongation at break is used to characterize its flexibility.

[0076] 2. Water-proof fog performance test: Fix the above film in a 60℃ constant temperature water bath, with the water surface about 5cm above the film and the ambient temperature at room temperature (23±2)℃. When the area of ​​fog droplets on the film is ≥50.0%, it is considered to be invalid. Record the effective time to characterize its long-term effectiveness.

[0077] 3. Light transmittance test: In accordance with the provisions of GB / T 2410-2008, the light transmittance of the above film samples was measured by spectrophotometer.

[0078] Table 1. Performance test results

[0079]

[0080] As shown in Table 1, the PVC plastics of Examples 1 to 7 have better mechanical properties and long-term anti-fogging properties than the PVC plastics of Comparative Examples 1 to 3. The reason may be that the anti-fogging additives used in the examples of the present application can, on the one hand, encapsulate the anti-fogging agent and play a slow-release role; on the other hand, they can play a plasticizing role and improve the mechanical properties of the PVC plastic, especially the flexibility.

[0081] Compared with Examples 5 to 7, Example 1 is more outstanding in the long-term anti-fog performance. The reason may be that the EVA-styrene-hydroxyacrylate copolymer can be effectively dispersed in the PVC resin matrix to form a polar dispersion, and the binding force on the anti-fog agent is enhanced by forming hydrogen bonds with the anti-fog agent, reducing its migration rate, thereby enhancing the long-term anti-fog performance of the PVC plastic.

[0082] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A fog-proof PVC plastic, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of polyvinyl chloride resin, 1-2 parts of heat stabilizer, 0.5-2 parts of lubricant, 2-4 parts of antifogging agent, 1-2 parts of antifogging auxiliary agent; The raw materials of the anti-fog auxiliary agent include cyclodextrin, diisocyanate and fatty acid polyol ester in a molar ratio of 1:5-12:8-15, wherein the fatty acid polyol ester has 1 hydroxyl group. The diisocyanate is used as a crosslinking agent to graft the fatty acid polyol ester onto the surface of cyclodextrin.

2. The PVC plastic according to claim 1, characterized in that: The fatty acid polyol ester includes one or more of diglycerol fatty acid ester, sorbitol fatty acid ester and polyethylene glycol fatty acid ester; the carbon number of the fatty acid is 10-20.

3. The PVC plastic according to claim 1, characterized in that: The diisocyanate is selected from one or more of toluene diisocyanate, diphenylmethane diisocyanate and hexamethylene diisocyanate.

4. The PVC plastic according to claim 1, characterized in that: The cyclodextrin molecule contains 6 to 8 D-pyranose units.

5. The PVC plastic according to claim 1, characterized in that: The preparation method of the anti-fog auxiliary agent is as follows: Add fatty acid polyol ester and diisocyanate to an organic solvent, heat to 50-60°C, stir and reflux at constant temperature for 1-2 hours, add cyclodextrin, heat to 60-80°C, stir and reflux at constant temperature for 3-7 hours; after the reaction is completed, reflux and wash with acetone, distill and recover the solvent after washing, and then dry the product to obtain.

6. The PVC plastic according to claim 1, characterized in that: The antifogging agent is fatty acid polyol ester and / or fatty acid polyoxyethylene ester.

7. The PVC plastic according to claim 1, characterized in that: The raw materials of the plastic also include 10 to 20 parts of EVA-styrene-hydroxy acrylate copolymer.

8. The PVC plastic according to claim 7, characterized in that: The EVA-styrene-hydroxy acrylate copolymer is obtained by melt grafting reaction of EVA, styrene and hydroxy acrylate in a mass ratio of 100:10-20:5-12 under the action of an initiator, and the reaction temperature is 160-190°C.

9. The PVC plastic according to claim 1, characterized in that: The heat stabilizer is an organic tin heat stabilizer.

10. A method for preparing anti-fog PVC plastic, characterized in that: The following steps are included According to the raw material ratio described in any one of claims 1 to 9, weigh PVC resin, heat stabilizer, antifogging agent, antifogging aid, and lubricant and add them into a mixer, heat to 110 to 130° C. and mix them evenly, then pass them into a cooling mixer and cool them down to discharge; The cooled blended material is passed into a twin-screw extruder for melt extrusion and granulation to obtain anti-fog PVC plastic.

Citation Information

Patent Citations

  • Sulfonate type reactive high polymer emulsifier and preparation method and application thereof

    CN104030947A

  • Crystallization controllable thermoplastic polyurethane material and preparation method thereof

    CN107141437A